Oil Load Reduction of Oilfield-Produced Water by Applying Swirl–Cyclonic Flotation: A Pilot-Scale Investigation - Liu, Jianfei; Wang, Huihui; Zhao, Yongfeng; Zhang, Yi; Zhao, Hongbing; Zhao, Weilong; Zhang, Yongsheng; Wang, Xiaowei; Li, Xue; Zhang, Ming (Frontiers in Environmental Science, 2022)
A swirl–cyclonic flotation (SCF) apparatus was fabricated by combining hydrocyclone and air flotation separation to reduce the oil droplet load of oilfield-produced water. The apparatus was designed as three concentric cylinders with functions of swirling, air-floating separation, and oil collection. Influencing factors such as influent flow, oil concentration, and aeration amount were investigated in the pilot-scale test. The oil concentration of the effluent was below 100 mg/L during continuous operation under the influent flow rate of 1.5 m3/h and aeration amount of 0.4 L/min without adding any chemicals. Results could be explained by the improvement in the floating velocity of oil droplets, resulting in oil load reduction. The oil and water separation mechanism of the SCF apparatus was determined by analysis of oil droplet size distribution. Compared with other flotation apparatus, the SCF apparatus had the advantages of high oil removal efficiency, low retention time, and stable water treatment quality. The apparatus also had no chemical agents added and had less floor area, leading to reduced chemical cost. The designed SCF apparatus have potential industrial application as pretreatment for oil–water load reduction.